Comparative Study on the Seed Health of Five Commonly Cultivated Wheat Varieties (Triticum aestivum L.) in Nepal - Sudip Ghimire; Santoshi Neupane; Rabin Kushma Tharu (AgroEnvironmental Sustainability)
Seed-borne pathogens can negatively affect wheat crop germination, plant health, and yield, making it essential to routinely test and treat seeds. Therefore, identifying seed-borne pathogens in commonly cultivated wheat varieties is vital to ensuring sustainable food production. The study sought at the Central Agriculture Laboratory in Lalitpur, Nepal, aimed to identify seed-borne pathogens in five commonly cultivated wheat varieties and evaluate their seed health. The study utilized the Standard Blotter Method to assess various parameters, including germination percentage, pathogen incidence percentage, shoot length, and seedling vigor index, in a controlled environment. The experiment used a complete randomized design with four replications and five treatments. Five wheat varieties (Gautam, Aaditya, Bijaya, Dhaulagiri, and NL971) were sown in Petri dishes containing blotting paper wetted with sterilized distilled water to assess the incidence and severity of Bipolaris sorokiniana. The data obtained were tabulated in Microsoft Excel and analyzed using Gen Stat. The study found that Gautam had the highest Bipolaris infection (18.25%), while NL971 had the lowest (11.25%), followed by Bijaya, Dhaulagiri, and Aaditya. Dhaulagiri had the highest germination percentage (99.50%), followed by Aaditya, Bijaya, and NL971, while Gautam had the lowest (79%). Aaditya demonstrated the highest shoot and root weight, shoot length, and seedling vigor index, while Gautam had the lowest. The study concluded that Gautam was vulnerable to low seed health, while Aaditya and other varieties demonstrated stronger seed health and resistance to the pathogen. These findings are crucial for improving seed health and ensuring sustainable food production in Nepal.